The Development and Validation of a Questionnaire to Assess Agility in Software Engineering (QASE) - Tchikanmou, Vincent; Tabea (Journal of Software Engineering Research and Development, 2026)
The concept of agility is increasingly becoming the focus of empirical research. However, what agility is and how it can best be conceptualized and measured remain controversial, even among researchers. This lack of consensus is reflected in the literature in the divergent approaches used to operationalize the concept in research, which limits the comparability of empirical results and impedes the development of a cohesive body of knowledge in the field. Against this background, the present article addresses the development of a valid questionnaire to assess agility in software engineering (QASE) that can be consistently used across various contexts. For this purpose, the commonalities among pioneer agile methods were examined by analyzing their underlying techniques, resulting in a second-order measurement model comprising 30 factors and 90 items. The QASE was evaluated using confirmatory factor analysis in a first study (N = 418), then refined and re-evaluated in a second study (N = 152), thereby demonstrating its factor structure, validity, and reliability. With the QASE, we provide the research community with a theoretically sound and empirically valid measurement instrument that facilitates hypothesis testing, supports theory development, and enables more reliable conclusions about the mechanisms underlying the positive outcomes associated with agility, thereby contributing to a more coherent and cumulative body of knowledge in Agile Software Development.